PERSPECTIVES ABOUT TRUTH. INTRODUCTION - TOMI, Paula (Studia Universitatis Babeș-Bolyai Philosophia, 2023)
Truth was always a central notion in philosophy. From an analytical perspective, the classical truth theories aimed to discover the underlying nature of truth. For example, the correspondence theory considers truth to be a relation between truth-bearers and truthmakers, while, the coherence theory of truth takes truth as being coherent with a specific set of beliefs. On the other hand, deflationary theories of truth - in general - tend to argue that there is no substantive nature of truth. According to those, truth can be defined in a trivial manner and its role is – at most – a logical one, the truth predicate being a purely logical device.